IFN-gamma, IL-5, IL-6 and IgE in patients infected with Giardia intestinalis. - Violetta Dymicka-Piekarska; Joanna Matowicka-Karna; Halina Kemona (Folia Histochemica et Cytobiologica, 2009)
The immune system, its cellular and humoral response, is engaged by the host organism to fight against parasitic infections. The study group consisted of 90 patients (58 women and 32 men), aged 18-72 years, infected with G. intestinalis. The diagnosis was established based on laboratory investigations (stool examination, choloscopy, GSA-65). Blood for analysis was collected before (G1), and 2 weeks (G2) and 2 months (G3) after antiparasitic treatment. Control group consisted of 40 healthy subjects (22 women and 18 men), aged 20-45 years. The concentrations of IgE were assayed using a set of VIDAS (bioMerieux) and the concentrations of IL-5, IL-6, IFN-gamma were determined using a set of Quantikine human (R&D Systems). It was revealed that in giardiosis the concentrations of IgE and IL-5 in blood serum were twice as high, the concentration of IL-6 was two and a half times higher and the concentration of IFN-gamma was almost four times higher as compared to healthy controls.